2019
DOI: 10.3390/jcm8030359
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Sepsis-3 Consensus Criteria in a Geriatric Acute Care Unit: A Prospective Study

Abstract: The prognostic value of quick Sepsis-related Organ Failure Assessment (qSOFA) score in geriatric patients is uncertain. We aimed to compare qSOFA vs. Systemic Inflammatory Response Syndrome (SIRS) criteria for mortality prediction in older multimorbid subjects, admitted for suspected sepsis in a geriatric ward. We prospectively enrolled 272 patients (aged 83.7 ± 7.4). At admission, qSOFA and SIRS scores were calculated. Mortality was assessed during hospital stay and three months after discharge. The predictiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 50 publications
2
18
0
5
Order By: Relevance
“…Whether the coronavirus exposure develops into a true infection might contrariwise depend on the individual's first-line abilities, and, regrettably, malnutrition is a common occurrence that afflicts many older adults in China (47) and Italy (48), both having been heavily afflicted by the highest number of deaths. It is clear that the segment of population most at risk of SARS-CoV-2 infection is the elderly, with frailty (49) and older age (50) being well-known predictors of a negative outcome in acute care settings. Intensive clinical monitoring at admission with subsequent tailored nutritional care is needed for COVID-19 patients, especially those with co-existing chronic conditions or medications that could further aggravate the nutritional status (51).…”
Section: Resultsmentioning
confidence: 99%
“…Whether the coronavirus exposure develops into a true infection might contrariwise depend on the individual's first-line abilities, and, regrettably, malnutrition is a common occurrence that afflicts many older adults in China (47) and Italy (48), both having been heavily afflicted by the highest number of deaths. It is clear that the segment of population most at risk of SARS-CoV-2 infection is the elderly, with frailty (49) and older age (50) being well-known predictors of a negative outcome in acute care settings. Intensive clinical monitoring at admission with subsequent tailored nutritional care is needed for COVID-19 patients, especially those with co-existing chronic conditions or medications that could further aggravate the nutritional status (51).…”
Section: Resultsmentioning
confidence: 99%
“…3 Anand et al 1 found that patients testing positive for the qSOFA were older and had more comorbidities, but it is not known how age and comorbidity affect the performance of the qSOFA. Bastoni et al 4 used the Rockwood Clinical Frailty Scale in predicting 1-and 3-month mortality in older patients admitted to a geriatric acute care unit and reported areas under the receiver operating curve of 0.775 and 0.756, respectively. Fernando et al 5 found an interaction between the qSOFA and Rockwood Clinical Frailty Scale in older patients admitted to the ICU with suspected infection, with an adjusted OR for in-hospital mortality of 7.54 when both were present.…”
Section: Can Qsofa Perform Better If Combined With Frailty Measures Imentioning
confidence: 99%
“…In the ED, we found the National Early Warning Score and the previous Systemic Inflammatory Response Syndrome criteria have greater prognostic value for 7-day mortality than the qSOFA. 3 Anand et al 1 found that patients testing positive for the qSOFA were older and had more comorbidities, but it is not known how age and comorbidity affect the performance of the qSOFA. Bastoni et al 4 used the Rockwood Clinical Frailty Scale in predicting 1-and 3-month mortality in older patients admitted to a geriatric acute care unit and reported areas under the receiver operating curve of 0.775 and 0.756, respectively.…”
Section: Can Qsofa Perform Better If Combined With Frailty Measures Imentioning
confidence: 99%
“…Although Fernando et al 2 demonstrated particularly high mortality in patients who were critically ill with both the qSOFA and frailty, Bastoni et al3 found that the prognostic accuracy of the qSOFA was poor in a geriatric acute care setting and comparable with the Systemic Inflammatory Response Syndrome criteria. Recently, Parks Taylor et al 4 also found decreasing predictive accuracy of the qSOFA with increasing comorbidity burden among patients admitted for suspected infection.…”
mentioning
confidence: 99%